Effects of different machine transplanting methods on the physiological and yield characteristics of late rice in China - Jia, Xuan; Li, Yonglei; Song, Jiannong; Liu, Cailing; Cao, Xiaolin; Chen, Licai; Wan, Lipengcheng; Ma, Xiang (International Journal of Agricultural and Biological Engineering, 2024)
To address problems caused by rice machine transplanting such as injury to the seedlings and recovery period that extend growth period, this study explored the effects of different machine transplanting methods on the physiological and yield characteristics of late rice in China, and determine the appropriate machine transplanting method for late rice, which was expected to provide a basis for high-yield and high-efficient cultivation of machine-transplanted late rice. Hybrid indica rice Taiyou 398 and conventional indica rice Jing Gangruanzhan were selected as the research objects, and large-pot carpet seedling machine transplanting (M1), conventional pot carpet seedling machine transplanting (M2) and ordinary carpet seedling machine transplanting (M3) were adopted respectively to analyze their effects on seedling quality, population physiological characteristics, yield and its components and economic benefits of late rice. The results showed that compared with M2 and M3, M1 achieved higher seedling quality, showing significant advantages in the early stage despite average root entwining force that met the requirement of machine transplanting. The seedlings transplanted using M1 had shorter recovery period after mechanical transplanting, with earlier tillering, earlier peak seedling, and slower declining of stems and tillers in the late stage; the peak seedling number was not high, but the effective tiller number and earbearing tiller percentage were significantly higher than those achieved by the other two machine transplanting methods. Also, M1 achieved stronger photosynthetic capacity of flag leaves before HS, with more photosynthetic products in stems and leaves transported to panicles and more efficiently after HS. Compared with seedlings transplanted using M2 and M3, the recovery period of those transplanted using M1 was shortened by 3 and 5 d, the heading stage (HS), and maturity stage (MS) were advanced, which effectively reduced the risk and impact of “cold dew wind” on machine-transplanted late rice. M1 had significant yield increase advantage and economic benefit, with better grain maturity, and “larger panicles, more panicles, more and fuller grains”. M1 achieved an average yield increase of 10.31%-11.10%, 20.67%-25.10% in 2 years, and an average income increase of 18.65%-131.06% and 62.85%-323.78%, respectively. Therefore, vigorously developing M1 is the key to the high-yield and high-efficient cultivation of machine-transplanted late rice in China. Keywords: large-pot carpet seedling, machine transplanting, late rice, physiological characteristics, seedling quality, yield DOI: 10.25165/j.ijabe.20231606.7764 Citation: Jia X, Li Y L, Song J N, Liu C L, Cao X L, Chen L C, et al. Effects of different machine transplanting methods on the physiological and yield characteristics of late rice in China. Int J Agric & Biol Eng, 2023; 16(6): 37–47.